Síntese e caracterização elétrica de blendas e compósitos de PMMA/PEG e PMMA/PEG/Na2WO4.2H2O - Maria, Roberta Patrícia Medeiros de (2015)
As energy demands were being presented and required by technological advances, the synthesis of new materials capable of meeting these needs, was and has been thoroughly studied and performed; among these materials are composite polymeric films that have stood out as an alternative chemistry, physics, electrical and economically viable. In this work self-supporting thin films of poly(methyl methacrylate) (PMMA) in the form of blends, linked to poly (ethylene glycol) (PEG), and composite doped with sodium tungstate dihydrate were obtained by combining the sol-gel methods and casting. The electrical, structural, chemical and morphological characterization of the films obtained was performed using electrochemical impedance spectroscopy (EIS) to obtain the electrical parameters, attenuated total reflection in the infrared (IR-ATR) and X-ray diffraction (XRD) to study the structural and chemical composition, while the thermal stability was evaluated using thermogravimetric analysis (TGA), differential thermal analysis (DTA) and differential scanning calorimetry (DSC); morphological and topographical characteristics of the films were analyzed by optical microscopy (OM) and scanning electron (SEM). The addition of the salt promoted standard modifications of the arrangement of the polymer chains, observed by X-ray diffraction and confirmed by the changes of the bands relative to the angular deformation -CH2- chain and asymmetric stretching -C-C-chain, suggesting structural changes in polymer chain. The miscibility between the polymers poly (methyl methacrylate) and poly (ethylene glycol) was a result of the presence of intermolecular interactions type hydrogen bonding between the PMMA and -CO- OH groups of the PEG and sodium tungstate salt, highlighted in analyzes by IR-ATR as well as purely electrostatic interactions. The systems showed better capacitive characteristics and larger relaxation times, favored by increasing the concentration of sodium tungstate, a result of improved sensitivity of the charges accumulated in the electrode.